Inspirational factors in adoption and production of Kachri (Cucumis callosus) on large scale in hot arid parts of western Rajasthan: An assessment (Indian Journal of Arid Horticulture, 2013)
The study was conducted in Bikaner district of western Rajasthan and inspirational factors, which encourage the  farmers to adopt and produce the kachri (Cucumis callosus) in hot arid eco-system, were assessed. The major inspirational  factors which motivate the farmers for the adoption and production of kachri on large scale in hot arid eco-system were  “substantial income from fresh fruits of kachri, substantial income from dried (dehydrated) kachri, low cost of cultivation,  minimum loss due to the attack of insects and diseases, very low water requirement of the crop, high seed germination  capacity of the crop, accessibility of drought hardy local varieties, the vegetables of mature kachri fruits is most favorite,  kachri vegetable has a special test and flavour, its preserved items are most liked and acceptable in the society, high demand  of kachri fruits in localities/ local markets/villages, high demand of value added products of kachri in the markets, very  good storage life of the fruit. Among the major factors which restrain the adoption and production of Kachri at large scale in  hot arid eco-system, were; scarcity of water, very low and erratic rainfall and occurrence of drought very frequently, lack  of viable schemes and support system for kachri growers, no standardized technique is available for value addition of kachri, very deep and salty ground water, inadequate supply of electricity, poor marketing system and market intelligence,  lack of knowledge and awareness among the farmers about improved technologies of Kachri cultivation.
Keywords: Kachri; inspiration factors; constraints in adoption